Purification of some industrial waste water contaminants entering the Caspian Sea basin using vetiver plant - Sahebeh Hajipour; Morteza Mohammadi Deylamani; Mohadeseh Momen Zadeh; Mansour Afshar Mohammadian (علوم محیطی)
Introduction: plant remediation is cost-effective and environmentally friendly, in which the plant uses its natural abilities to restore the environment. Plants used for phytoremediation must have the ability to accumulate large amounts of metal pollutants without causing toxicity in them. Today, with the increase in the world's population and the development of industries and factories, the amount of wastewater entering the environment, which often contains heavy metals and various pollutants, increases. Heavy metals have destructive effects on the health of plants and animals in different ecosystems. Considering the ability of heavy metals to accumulate and cause toxicity in living organisms, this type of pollution is considered a serious and fundamental problem. The use of plants as an effective and cost-effective technology to remove metal pollutants from contaminated soils and waters has been recommended as a new method instead of other costly measures. Therefore, the removal of pollutants from soil and polluted waters with the help of plants through absorption and accumulation in roots, stems and leaves is considered as one of the purification methods to remove metal pollutants. In this process, choosing the right plant with high absorption capacity and compatible with the environment, without negative environmental effects, plays a very effective role in the amount of pollutant purification.Material and methods: In this regard, in order to investigate the uptake and accumulation of heavy metals by plants, an experiment was conducted in a completely randomized design with three replications using vetiver plant. Plants treated with industrial effluent and control plants were irrigated with municipal water. Also, pots containing soil without plants were considered to measure the amount of elements in the soil during the six-month experiment period, they were regularly irrigated with other pots with industrial effluent. In order to investigate the effect of irrigation with effluent on the yield of vetiver plant, after a six-month period of experiment, heavy element analysis and anatomical and physiological studies were performed on plants treated with industrial effluent and control plants. Transfer and accumulation factors, which are two important factors in measuring plant ability for phytoremediation, were also examined.Results and discussion: The results of this study showed that among the most heavy metals in industrial effluents, which included zinc and chromium, most of the mentioned elements were stored in the roots of vetiver and less were collected in the aerial parts. Also, the results of physiological traits experiments showed that the factors of soluble sugars and proline in the treated plants increased compared to the control and the concentration of malondialdehyde in the treated plants decreased compared to the control. The results of root studies in control and treated plants showed that root diameter, central cylinder diameter and number of vascular clusters in treated plants increased compared to control.Conclusion: Overall, the results of this study showed that in the process of absorption of heavy metals, changes were made in some anatomical and physiological traits of treated plants. Examination of transfer and bioaccumulation factors also showed that vetiver has the ability to absorb zinc and chromium through plant stabilization.